Effectiveness of an intervention to overcome influenza vaccine hesitancy in specialty clinic patients. Issue 30 (29th July 2022) - Webb, Nathaniel J.; Lindsley, Joshua; Stockbridge, Erica L.; Workman, Ashleigh; Reynolds, Conner D.; Miller, Thaddeus L.; Charles, Jean; Carletti, Michael; Casperson, Stefanie; Weis, Stephen
Abstract : Background: Individuals on immunosuppressive therapies experience greater morbidity and mortality due to vaccine-preventable illnesses, but there are low rates of adherence to immunization guidelines within this population. Objective: To determine the effectiveness of clinician-led education, patient-centered dialogue, and immediately available immunization on influenza vaccination uptake in patients taking immunosuppressive therapies. Method: We used a controlled before-and-after quasi-experimental design to evaluate our quality improvement intervention occurring from September 2019 to March 2020, with follow-up through July 2020. The study included 2 dermatology practices wherein nursing staff offered influenza vaccination during patient rooming (standard care). Within each practice, clinicians either implemented the intervention or provided only standard care. Patients received the intervention or standard care depending on the clinician they visited. Patients seen at the 2 clinics during the intervention period were included in analyses if they were taking or newly prescribed immunosuppressant medication at the time of their visit. We examined influenza immunization status for 3 flu seasons: 2017–2018 (preintervention), 2018–2019 (preintervention), and 2019–2020 (intervention). Intervention: Immunosuppressed patients initially declining an influenza vaccine were provided dermatologist-led education on the benefits of immunization. Dermatologists explored and addressed individual patients' immunization concerns. Influenza vaccination was then offered immediately postdialogue. Results: Analyses included 201 dermatology patients who were prescribed or currently taking immunosuppressive medication (intervention group [72.6%], comparison group [27.4%]). During the intervention period, 91.1% of the intervention group received influenza vaccination compared to 56.4% of the comparison group. Vaccination trends from 2018–2019 (preintervention) to 2019–2020 (intervention) differed significantly between groups (χ 2 = 22.92, P < .001), with greater improvement in the intervention group. In 2019–2020, influenza vaccination was more likely in the intervention group relative to the comparison group (odds ratio: 16.22, 95% confidence interval: 5.55–47.38). In the subset of patients that had never received an influenza vaccine, influenza immunization in 2019–2020 was more common in the intervention group (75.8%, 25/33) relative to the comparison group (13.3%, 2/15, P < .001). Conclusion: The intervention successfully addressed vaccine hesitancy and improved influenza immunization rates in an immunosuppressed population receiving care from a specialty clinic. Implementing a similar model across specialty clinics may improve vaccination rates for influenza, coronavirus disease 2019, and other vaccine-preventable illnesses in other populations.